2009
DOI: 10.1007/s10750-009-0039-8
|View full text |Cite
|
Sign up to set email alerts
|

Riverine habitat heterogeneity: the role of slackwaters in providing hydrologic buffers for benthic microfauna

Abstract: Slackwater habitats within lowland rivers support abundant biotic communities and provide these communities with a refuge from increases in discharge. These refuges allow biota to persist as discharges, vary and provide a source of colonists for slackwaters further downstream. In order to investigate the response of slackwater benthic microfaunal communities to changes in discharge, artificial slackwaters were created within the main channel of a lowland river and benthic microfaunal communities were sampled o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Therefore, the values of all hydrological parameters were increased, including the depth, which according to CCA also positively influenced the zooplankton biomass. More water with greater width and depth causes floodplains and slack waters, which are a source of zooplankton in the river current (Saunders & Lewis 1998, Nielsen et al 2010. Thus, the more slack waters connected with a river, the more quantity of zooplankton in the river current.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the values of all hydrological parameters were increased, including the depth, which according to CCA also positively influenced the zooplankton biomass. More water with greater width and depth causes floodplains and slack waters, which are a source of zooplankton in the river current (Saunders & Lewis 1998, Nielsen et al 2010. Thus, the more slack waters connected with a river, the more quantity of zooplankton in the river current.…”
Section: Discussionmentioning
confidence: 99%
“…The richest sources of zooplankton are lakes, reservoirs, floodplains, and ponds (Ejsmont-Karabin & Węgleńska 1996, Lair 2006, Chang et al 2008, Czerniawski & Pilecka-Rapacz 2011. Much less productive sources of zooplankton in rivers are wetlands and slackwaters (Richardson 1992, Nielsen et al 2010. Irrespective of the source, after reaching the main watercourse over a certain section of the river zooplankton suffers qualitative and quantitative reduction, which is most pronounced for large crustaceans (Armitage & Capper 1972, Walks & Cyr 2004.…”
Section: Introductionmentioning
confidence: 99%
“…River plankton ecologists are also interested in how the river zooplankton community in the main channel is modified by the inflow from the slackwaters [4,16], floodplains [28] connected reservoirs [24,29,30] and tributaries [8]. How much the zooplankton communities are reduced between upstream and downstream sections, especially below lake outlets, [3,5,9,29] is another major point of interest.…”
Section: Discussionmentioning
confidence: 99%
“…The greater the width and depth of the river, the more small floodplains and slackwaters there are, which play a very important role in zooplankton reproduction. These small water bodies also help move the zooplankton to the main channel [1,15,16]. Nielsen et al [16] have observed that the abundance of adult microcrustaceans even exceeded 180 ind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation